Grasping intersubjectivity: an invitation to embody social interaction research - Jaegher, Hanne de; Pieper, Barbara; Clénin, Daniel; Fuchs, Thomas (Phenomenology and the cognitive sciences, 2017)
Underlying the recent focus on embodied and interactive aspects of social understanding are several intuitions about what roles the body, interaction processes, and interpersonal experience play. In this paper, we introduce a systematic, hands-on method for investigating the experience of interacting and its role in intersubjectivity. Special about this method is that it starts from the idea that researchers of social understanding are themselves one of the best tools for their own investigations. The method provides ways for researchers to calibrate and to trust themselves as sophisticated instruments to help generate novel insights into human interactive experience. We present the basics of the method, and two empirical studies. The first is a video-study on autism, which shows greater refinement in the way people with autism embody their social interactions than previously thought. The second is a study of thinking in live interactions, which provides insight into the common feeling that too much thinking can hamper interaction, and into how this kind of interactional awkwardness might be unblocked.